Economic, Financial and Social Structure in Diyarbakır During the Transition Period of Republican Phase - Tahir Öğüt; Çiğdem Çadırcı (Gazi Akademik Bakış)
Diyarbakır, after a long imperial experience and in the transition to the Republican period that represents the beginning of a reformist phase, will continue to be administrative, cultural and economic center in accordance with its historical position. Although developmental approaches have been tried to apply during the Ottaman period, it has been stayed away to achieve the objectives due to the deficiencies in the social structure, administrative and financial problems. With the transition to Republican phase, “Birinci Umum-i Müfettişlik” taking public intervention in the center with a regional developmental approach is going to be established. This gives significant clues about overcoming the economic development of Southeastern Anatolia as well as on the general developmental geographic-based political approach of the public. However, the nature of the inherited social structure, financial applications, factors such as industrial and agricultural production factors will be decisive in the struggle to the problem of development in Diyarbakır.